Decoupling of priming and microbial N mining during a short-term soil incubation. (February 2019) - Wild, Birgit; Li, Jian; Pihlblad, Johanna; Bengtson, Per; Rütting, Tobias
Abstract: Soil carbon (C) and nitrogen (N) availability depend on the breakdown of soil polymers such as lignin, chitin, and protein that represent the major fraction of soil C and N but are too large for immediate uptake by plants and microorganisms. Microorganisms may adjust the production of enzymes targeting different polymers to optimize the balance between C and N availability and demand, and for instance increase the depolymerization of N-rich compounds when C availability is high and N availability low ("microbial N mining"). Such a mechanism could mitigate plant N limitation but also lie behind a stimulation of soil respiration frequently observed in the vicinity of plant roots ("priming effect"). We here compared the effect of increased C and N availability on the depolymerization of native bulk soil organic matter (SOM), and of 13 C-enriched lignin, chitin, and protein added to the same soil in two complementary ten day microcosm incubation experiments. A significant reduction of chitin depolymerization (described by the recovery of chitin-derived C in the sum of dissolved organic, microbial and respired C) upon N addition indicated that chitin was degraded to serve as a microbial N source under low-N conditions and replaced in the presence of an immediately available alternative. Protein and lignin depolymerization in contrast were not affected by N addition. Carbon addition enhanced microbial N demand and SOM decomposition rates, but significantly reduced lignin, chitin, and protein depolymerization. Our findings contrast the hypothesis of increased microbial N mining as a key driver behind the priming effect and rather suggest that C addition promoted the mobilization of other soil C pools that replaced lignin, chitin, and protein as microbial C sources, for instance by releasing soil compounds from mineral bonds. We conclude that SOM decomposition is interactively controlled by multiple mechanisms including the balance between C vs N availability. Disentangling these controls will be crucial for understanding C and N cycling on an ecosystem scale. Highlights: Low N and high C availability might boost soil N-polymer breakdown ("N mining"). N mining might thus lie behind higher soil respiration near plant roots ("priming"). We tested the effect of C and N input on the degradation of SOM and added polymers. C input increased SOM degradation but reduced that of chitin, lignin and protein. Our findings challenge the hypothesis of N mining as a key driver of priming.